Fiction Publishing Patterns in the “Wattpad” Online Community - Siti Herdiani Nurkhodijah; Tine Silvana Rachmawati; Andri Yanto (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
Wattpad is a community website that allows people to find stories from authors of various genres. This study aims to determine the pattern of fiction publishing in the Wattpad online community. This study uses a qualitative method with a case study approach. The research data were obtained through three (3) informants who were productive fiction writers on Wattpad. The results show that the writers on Wattpad get ideas from an open-minded/objective view of many things, the environment, and experiences that are supported by information. The process of publishing starts from creating an account then filling in the details of the story, till publishing it. There are two types of publishing processes, namely the author submits the manuscript to the publisher or publisher who contacts the author. Apart from being published, some have been made into cinema films. This research concludes that writers on Wattpad can get story ideas from anywhere and then develop them into stories, while the publication process on Wattpad has no special rules because everything is based on the author and the existence of publications from Wattpad to other media such as a publishing and being made into cinema films.